Desain Simulasi Berbasis Visual Basic Application (VBA) Spreadsheet Excel pada Materi Polarisasi Gelombang Linier dan Non Linier - Fitri April Yanti (U-Teach: Journal Education of Young Physics Teacher, 2023)
The purpose of this research was to design a Visual Basic Application (VBA) Excel Spreadsheet based simulation on linear and non-linear wave polarization material that is feasible for physics education students. This study uses the type of research and development. The ADDIE model was chosen in this study, which includes: analysis, design, develop, implementation, and evaluation. However, this design stage only goes through the stages: analysis, design, develop. The research data were obtained by means of interviews and validation questionnaires. 10 physics education students were the subject of a limited trial in this study. Data were analyzed with quantitative descriptive. The results showed that the Excel Spreadsheet based Visual Basic Application (VBA) simulation on linear and non-linear wave polarization material for physics education students was stated to be valid and usable. It was concluded that the results of this design were accurate and could be utilized by physics education students